Objektifikasi Perempuan dalam Lirik Lagu “Dua Sedjoli” Dewa 19: Analisis Wacana Kritis Norman Fairclough - Arnetta Prameswari Sholihati; Adiska Putria Nova (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Popular songs function not only as entertainment but also as cultural media that reproduce ideology and social constructions, including gender relations. This study aims to reveal the objectification of women in the lyrics of Dua Sedjoli by Dewa 19 using Norman Fairclough's Critical Discourse Analysis. Employing a descriptive qualitative approach, the study examines textual, discursive practice, and social practice dimensions. The findings indicate that the lyrics construct women as objects through ownership metaphors, imperative expressions, and religious legitimization that position men as dominant subjects. Discursive practice demonstrates that production, distribution, and audience reception normalize romantic narratives that conceal power relations. At the level of social practice, female objectification is reproduced through patriarchal values embedded in popular music. This study concludes that Dua Sedjoli functions as a discursive practice that subtly perpetuates male hegemony through the aesthetics of romantic lyrics.